Doing It Right: A Rule Of Law Critique Of Privatization Methodology In Nigeria - Amadi, Sam (Journal of Sustainable Development Law and Policy, 2025)
This article undertakes a rule of law critique of privatization as economicreform policy in Nigeria. The rule of law approach interrogates not just thepolicy rationales of the programme but also its methodology. The articledistinguishes between a formal and substantive justice conception of rule oflaw and argues that the substantive justice conception of rule of law and itspolicy imperatives, sourced from the Fundamental Objectives and DirectivePrinciples of State Policy in Chapter 2 of the 1999 Constitution, provides averitable framework to realize the strategic goals of privatization in Nigeria.